Dynamic associations between anxiety, stress, physical activity, and eating regulation over the course of a behavioral weight loss intervention. (1st January 2022) - Smith, Kathryn E.; Mason, Tyler B.; Wang, Wei-Lin; Schumacher, Leah M.; Pellegrini, Christine A.; Goldschmidt, Andrea B.; Unick, Jessica L.
Abstract: Negative emotional experiences are associated with dysregulated eating behaviors that impede weight management. While weight loss interventions promote physical activity and self-regulation of eating, no studies have examined how physical activity may directly influence eating by attenuating associations between negative emotions and eating. Objective : The current study examined how momentary negative emotions (stress and anxiety), moderate-to-vigorous intensity physical activity (MVPA), and their interactions predict eating dysregulation (i.e., intensity of eating temptations, inability to resist eating tempting foods, overeating), as well as how these associations change during a weight loss intervention. Methods : Women with overweight/obesity ( N = 55) completed 14-day ecological momentary assessment (EMA) protocols with objective measurement of physical activity (i.e., bout-related MVPA time) before and after a three-month internet-based weight loss program. Results : Three-way interactions emerged predicting overeating and eating tempting foods. When women experienced higher than usual levels of momentary anxiety or stress at end-of-treatment, they were less likely to subsequently overeat or eat tempting foods when they had recently engaged in more MVPA (relative to their usual level). No significant associations were found for ratings of temptation intensity. Conclusions : Findings suggest MVPA may exert direct effects on eating regulation. Specifically, MVPA appears to increasingly buffer the effect of negative emotional states on dysregulated eating behavior over the course of a weight loss intervention. Future work is needed to develop ways of communicating to patients how activity can have both indirect and direct effects on body weight, and examine whether such knowledge improves outcomes.